2009
DOI: 10.1007/s00198-009-1037-4
|View full text |Cite
|
Sign up to set email alerts
|

Femur ultrasound (FemUS)—first clinical results on hip fracture discrimination and estimation of femoral BMD

Abstract: QUS measurements at the proximal femur are feasible and show a good performance for hip fracture discrimination. Given the promising results, this laboratory prototype should be reengineered to a clinical applicable instrument. Our results show promise for further enhancement of QUS-based assessment of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…The feasibility of in vivo quantitative ultrasound (QUS) measurements at the hip has been demonstrated, with a good clinical performance for hip fracture discrimination. (22,23) Interestingly-and similar to results previously obtained at the finger phalanges (24) -a thorough analysis of signals transmitted through the proximal femur suggested that different propagation pathways through the trabecular or cortical compartments could be identified, leading to the concept of multimodal QUS assessment of the proximal femur, by which both the trabecular and the cortical compartments could be assessed separately. Simulation studies of measurements at the proximal femur QUS (25) predicted the existence of a guided wave propagating circumferentially exclusively in the cortical shell of the neck.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…The feasibility of in vivo quantitative ultrasound (QUS) measurements at the hip has been demonstrated, with a good clinical performance for hip fracture discrimination. (22,23) Interestingly-and similar to results previously obtained at the finger phalanges (24) -a thorough analysis of signals transmitted through the proximal femur suggested that different propagation pathways through the trabecular or cortical compartments could be identified, leading to the concept of multimodal QUS assessment of the proximal femur, by which both the trabecular and the cortical compartments could be assessed separately. Simulation studies of measurements at the proximal femur QUS (25) predicted the existence of a guided wave propagating circumferentially exclusively in the cortical shell of the neck.…”
Section: Introductionsupporting
confidence: 69%
“…(22) The prototype scanner uses spherically focused transducers moving in a 2D scan to achieve an image of QUS variables (attenuation and speed of sound) at the proximal femur. With this approach, different regions can be measured, such as the great trochanter, the shaft, or the surrounding soft tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, aBMD alone is not sufficient to account for bone strength [3,4]. The development of a quantitative ultrasound (QUS) hip scanner [5,6] aims at providing an alternative to aBMD measurements. Because the cortical shell at the proximal femur determines a large part of bone strength [7,8], there is substantial interest in developing QUS measurements with improved sensitivity to cortical bone geometrical and material properties.…”
Section: Introductionmentioning
confidence: 99%